Frequency of Ischemic Heart Disease in End Stage Kidney Disease patients. - Shaikh, Shazaib; Memon, Shoukat; Saeed, Faiza; Chughtai, Javeria; Rehman, Gohar; Alam, Ashar; Imtiaz, Salman (Pakistan Journal of Kidney Diseases, 2025)
Introduction: Ischemic heart disease commonly coexists with end-stage kidney disease (ESKD), presenting significant challenges in patient management. This comorbidity elevates the risk of cardiovascular complications and mortality in individuals with ESKD. The complex interplay between these conditions highlights the need for comprehensive care and tailored interventions to reduce associated risks and improve patient outcomes. Materials and Methods: Eligible individuals at our hospital, were recruited based on inclusion/exclusion criteria. Informed consent was obtained, ensuring awareness of the study’s methods, risks, and benefits. Demographic data, medical history, physical examination, and ECG were recorded to assess ischemic heart disease. Results: The mean ± SD age of the participants was 49.84 ± 11.86 years. Among them, 73 (57.5%) were male, while 54 (42.5%) were female. Ischemic heart disease was identified in 88 (69.3%) of the patients. Conclusion: Ischemic heart disease is highly prevalent in end-stage renal disease patients, emphasizing the need to manage their elevated cardiovascular risk. Further research and targeted interventions are crucial for improving outcomes in this population.